The big Lebowski [videorecording (Blu-Ray)] - Bridges, Jeff, 1949-; Goodman, John, 1952-; Moore, Julianne; Coen, Joel (Universal Studios Home Entertainment, 2011)
Jeff "The Dude" Lebowski is pulled into the seedy underworld of criminal Los Angeles when two incompetent mobsters mistake him for an evil millionaire with the same name.